2018
DOI: 10.1002/dev.21788
|View full text |Cite
|
Sign up to set email alerts
|

Early parenting predicts hippocampal subregion volume via stress reactivity in childhood

Abstract: Rodent models indicate that parenting shapes offspring outcomes by programming the hypothalamic–pituitary–adrenal axis response to stress and, ultimately, altering brain structure and function. The present study tested this hypothesis and explored possible timing‐dependent associations in a longitudinal sample of children (N = 63). At Time 1 (M = 4.23 ± 0.84 years) and Time 2 (M = 7.20 ± 0.89 years), children completed parent–child interaction tasks and a laboratory stressor after which salivary cortisol sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 95 publications
0
20
0
Order By: Relevance
“…Recent work further suggests these effects may vary across subregions in early-to mid-childhood (i.e., Blankenship et al, 2019). An improved understanding of the typical developmental trajectories of hippocampal subregion development will allow future research to identify whether trajectories are impacted by factors, such as stress or disease, as indicated by accelerated or deviant trajectories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work further suggests these effects may vary across subregions in early-to mid-childhood (i.e., Blankenship et al, 2019). An improved understanding of the typical developmental trajectories of hippocampal subregion development will allow future research to identify whether trajectories are impacted by factors, such as stress or disease, as indicated by accelerated or deviant trajectories.…”
Section: Discussionmentioning
confidence: 99%
“…This structure also shows heightened plasticity and susceptibility to environmental influences compared to other regions in the brain. For example, the hippocampus has been shown to be impacted by the psychosocial stress associated with maltreatment (Teicher, Anderson, & Polcari, 2012) and also by more typical variations in caregiving (Blankenship, Chad-Friedman, Riggins, & Dougherty, 2019;Humphreys et al, 2019;Luby et al, 2012;Rao et al, 2010). Moreover, research suggests this plasticity is greatest during early childhood (see Tottenham & Sheridan, 2010 for review).…”
Section: Introductionmentioning
confidence: 99%
“…Associations between parental harshness and children's striatal structure may depend on whether parental harshness was measured during a sensitive period of enhanced striatal susceptibility to environmental effects (Blankenship, Chad‐Friedman, Riggins, & Dougherty, ). Dorsal and ventral striatal structure continues to develop across the ages studied here (Wierenga et al, ), with regionally heterogeneous developmental trajectories (Raznahan et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The internal consistency (W1 W2 ICC = 0.96, n = 28) were acceptable. Coding procedures have been previously detailed in other papers (Blankenship et al, 2018;Dougherty et al, 2013). Observed parental hostility demonstrated moderate stability from W1 to W2 (r = 0.51, p < 0.001).…”
Section: Parenting Behaviormentioning
confidence: 99%
“…2011; Frye et al, 2010;Gold et al, 2016;Hanson et al, 2010;Kelly et al, 2013Kelly et al, , 2015Kelly et al, , 2016Lim et al, 2014;McLaughlin et al, 2014;Rao et al, 2010;Tomoda et al, 2009;Whittle et al, 2009). The majority of studies have focused on severe forms of abuse and neglect (e.g., Andersen et al, 2008;Gold et al, 2016;Kelly et al, 2015;McLaughlin et al, 2014;Mehta et al, 2009), while a burgeoning literature has examined associations between normative variations in negative parenting and children's brain structure (Blankenship et al, 2018;Frye et al, 2010;Merz et al, 2019;Rao et al, 2010;Whittle et al, 2009Whittle et al, , 2016. Our lab has previously shown that normative variations in negative parenting were associated with hippocampal subregion volume (Blankenship et al, 2018) and the cumulative exposure of risks in the environment was associated with decreased cortical thickness (Chad-Friedman et al, 2020), providing further support for the influence of normative variations in negative parenting on children's brain structure.…”
mentioning
confidence: 99%